2021
DOI: 10.1039/d0cc07750j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in nanomaterial-based augmented sonodynamic therapy of cancer

Abstract: This review focuses on recent advances in augmented sonodynamic therapy (SDT) using engineered nanomaterials, and the mechanism of SDT for discussing future perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 124 publications
0
57
0
Order By: Relevance
“…Silicon is a part of various body tissues and is mostly important for bones, cartilage, and connective tissue well-being with a total amount of 7 g in the human body. Currently, a variety of SiNPs is developed for different biological applications [18][19][20]. Biodegradability and biocompatibility as well as the possibility to obtain SiNPs of various structures make silicon a promising material for use in the various fields of science, technology, and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon is a part of various body tissues and is mostly important for bones, cartilage, and connective tissue well-being with a total amount of 7 g in the human body. Currently, a variety of SiNPs is developed for different biological applications [18][19][20]. Biodegradability and biocompatibility as well as the possibility to obtain SiNPs of various structures make silicon a promising material for use in the various fields of science, technology, and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the sonosensitizer in conjunction with the US promotes the apoptosis of tumor cells. SDT is effective in treating a variety of tumors (Um et al, 2021). Recently, the application of SDT has been studied extensively (Wang et al, 2021), and our team also showed that SDT could promote cell apoptosis through the mitochondrial pathway in HCC cells (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 75%
“…Sonodynamic therapy (SDT) consists of the synergetic action between sound and a chemical agent, usually to trigger the release of reactive oxygen species (ROS) to induce cellular damage [ 85 , 86 , 87 ]. SDT partly relies on intratumoral oxygen availability, which is a specific challenge in the pancreas due to the intrinsic hypoxia in PDAC.…”
Section: Sonodynamic Therapymentioning
confidence: 99%